Ethical leadership and positive work behaviors: a conditional process model. Issue 3 (19th March 2020) - Li, Chaoping; Bao, Yuanjie
Abstract : Purpose: This study's purpose is to examine ethical leadership's effect on followers' positive work behaviors, as mediated by prosocial motivation and moderated by job autonomy. Design/methodology/approach: Two-wave survey data were collected from 200 Chinese employees working in various industries. A hierarchical regression and a bootstrapping test were used to test the hypotheses. Findings: Ethical leadership is positively related to followers' positive work behaviors, and prosocial motivation partially mediates this relationship. Job autonomy moderates the relationship between ethical leadership and prosocial motivation, as well as the indirect effect of ethical leadership on positive work behaviors via prosocial motivation. Research limitations/implications: The findings' generalizability is limited because only Chinese employees were investigated and a snowball sampling method was used. Future research should utilize other sampling methods and explore other contexts to determine whether the results can be replicated. Practical implications: Organizations should provide employees with greater behavioral discretion to benefit from the positive effects of ethical leadership. They should use selection and job design tools to boost their employees' prosocial motivation. Originality/value: The extant literature has largely applied the cognitive process approach to link ethical leadership and positive behaviors, treating ethical leadership as a risk-reducing or reciprocity-inducing factor. This study introduces a responsive process approach whereby prosocial motivation is established as a mediator between ethical leadership and positive work behaviors. Also, job autonomy is identified as a boundary condition of ethical leadership's effect.